Molecular size-fraction and seasonal characteristics of dissolved trace metals in river and estuarine waters of the Yellow River, China - Luan, Feng; Yang, Tingting; Lu, Yuxi; Wang, Ning (Frontiers in Marine Science, 2022)
The colloidal phase is an important metal storage form in the aquatic system. However, its biogeochemical behavior in the estuarine environment has been seldom studied. In this study, spatial variations, sources and correlations with seawater environmental factors of the dissolved Fe, Mn, Cu, Zn, Cd and Pb in the surface water of the Yellow River Estuary in China were investigated. The clean sampling system, centrifugal ultrafiltration technique, and ICP-MS were combined and used for the determination of the colloidal distribution of six metals in this region. Two stations of Zn in autumn had contamination factor values >1, which indicates lower contaminant levels of Cu, Zn, Cd and Pb. Dissolved target metal was divided into five fractions, i.e. <1 kDa, 1-3 kDa, 3-10 kDa, 10-100 kDa and 100 kDa-0.45 μm, while the average concentrations of each fraction were 60.17, 46.54, 47.73, 251.03, 1.44 and 1.08 nmol L-1 in spring and 62.30, 48.18, 15.35, 203.05, 1.20 and 1.70 nmol L-1 in autumn, respectively. The results showed that colloidal Mn, Cu, Zn, Cd and Pb might be dominated by high-molecular-weight fraction (100 kDa-0.45 μm). Additionally, the contribution of low-molecular-weight colloidal Fe (1-10 kDa) in this aquatic system was obvious. The addition in the colloidal and total dissolved fraction might be mainly related to particle-desorbed ligand, which was usually occurred in the middle salinity area. Dissolved organic carbon (DOC) and colloidal organic carbon (COC) concentration could not correlate with the behavior of Mn, Zn and Cd, which proved that the influence of inorganic ligands was higher than that of organic ligands or biological contributions, but the influence of salinity, dissolved oxygen (DO), pH and temperature should not be ignored. Overall, the results suggested that the occurrence of dynamic behaviors of colloidal metal in the YRE was highly associated with the salinity transition and formation of the organic matter-particle mixture system under complex hydrodynamic processes.